VERB WORD CLASSIFICATION BASED ON SEMANTIC TENDENCIES - Mahsudova Umida Abdusattar’s daughter (Galaxy International Interdisciplinary Research Journal, 2022)
The article attempts to study verb semantics and the content of words belonging to the verb-word group, describe it and its place in the language system, the direction of meaning of verbs and the classification of subjects and objects with which they come into contact.